Improvement of the Sharia Economy Through Digitalization of the Economy in Indonesia - Zainal Arif (Universitas Dharma Wacana, 2022)
The emergence of the Covid-19 pandemic has encouraged technological progress and digitalization so that later there was a change in people’s consumption patterns to become completely online. This has resulted in various financial sectors trying to integrate and adapt to advances in technology and digitalization, including sharia-based industry players. This research was carried out to see the developments and improvements that occurred in the Islamic Economy as a result of the emergence of economic digitization in Indonesia. This research will be carried out using a qualitative approach and data from various research results and previous studies still relevant to this research. The results of this study found that there was an increase in Islamic finance. This is because the emergence of the digitalization era makes it easy to do things, including conveying information. The players from the Islamic finance industry will be able to convey their information to the public more easily, and the majority of the Indonesian population is Muslim, thus causing the rapid development of the Islamic Economy in this era of economic digitization